On the inverse gamma as a survival distribution. - Glen, Andrew G. (Journal of Quality Technology)
This paper presents properties of the inverse gamma distribution and how it can be used a a survival distribution. A result is included that shows that the inverse gamma distribution always has an upside down bathtub (UBT) shaped hazard function, thus adding to the limited number of available distribution with this property. A review of the utility of UBT distributions is provided as well. Probabilistic properties are presented first, followed by statistical properties to demonstrate its usefulness as a survival distribution. As the inverse gamma distribution is discussed in a limited and sporadic fashion in the literature, a summary of its properties is provided in an appendix.